2014
DOI: 10.1590/2237-6089-2013-0054
|View full text |Cite
|
Sign up to set email alerts
|

Mothers who were sexually abused during childhood are more likely to have a child victim of sexual violence

Abstract: Introduction: Recurrent exposure to childhood sexual abuse (CSA) seems to be higher among victims of sexual abuse. In this sense, experiences related to sexual violence can perpetuate within the family context itself in various ways. Here, we investigate the association between being exposed to CSA and having a child victim of sexual abuse. Method: We used a sample with 123 mothers, who were divided into 2 groups: one consisting of 41 mothers of sexually abused children and another consisting of 82 mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Childhood sexual abuse has impacts across familial generations in terms of the likelihood of sexual victimization (McCloskey, 2000). There is converging evidence of intergenerational patterns of risk and mothers who are CSA survivors are up to 3.6 times as likely to have children who are also exposed to sexual violence compared to mothers who were not abused (Oates et al, 1998; McCloskey, 2000; Testa et al, 2011; Wearick-Silva et al, 2014; Testoni et al, 2018). Indeed, links in CSA risk spanning three generations have even been documented (Leifer et al, 2004; McCloskey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood sexual abuse has impacts across familial generations in terms of the likelihood of sexual victimization (McCloskey, 2000). There is converging evidence of intergenerational patterns of risk and mothers who are CSA survivors are up to 3.6 times as likely to have children who are also exposed to sexual violence compared to mothers who were not abused (Oates et al, 1998; McCloskey, 2000; Testa et al, 2011; Wearick-Silva et al, 2014; Testoni et al, 2018). Indeed, links in CSA risk spanning three generations have even been documented (Leifer et al, 2004; McCloskey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is remarkable that half of the participants have also experienced sexual abuse when growing up, a higher prevalence than what is usually observed in the general population (Alaggia et al, 2019;Barth et al, 2013;Singh et al, 2014). Previous studies have shown that mothers who were sexually abused during childhood are more likely to have a child victim of sexual violence (Borelli et al, 2019;Wearick-Silva et al, 2014). Usually, when mothers are also victims of sexual abuse themselves, not only do they feel overwhelmed and shocked by their child's disclosure of the violence but also feel confused about how to deal with their own emotions.…”
Section: Discussionmentioning
confidence: 98%